106k views
3 votes
Which expression is equivalent to ​

Which expression is equivalent to ​-example-1
User Gnanavel
by
6.3k points

2 Answers

4 votes

Answer:


(p^2)/(r)

Explanation:

Using the rules of exponents


(a^mb^n)^(p) =
a^(mp)
b^(np)


a^(-m) =
(1)/(a^(m) )


(p^10r^-5)^(1/5)

=
p^(10(1/5)) ×
r^(-5(1/5))

= p² ×
r^(-1)

= p² ×
(1)/(r)

=
(p^(2) )/(r)

User Lorenza
by
6.1k points
5 votes

Answer:

A

Explanation:

(P^10r^-5)^(1/5)

= p^(10×1/5) × r^(-5×1/5)

= p^2 × r^-1

= p^2/r

User Maksim Kondratyuk
by
5.9k points